Nejanilini Lake region (Manitoba, Canada) peat core data (2008-2009) - Philip Camill (Arctic Data Center, 2016)
This dataset contains metadata, chronologies, vegetation and physical/geochemical data for 25 peat cores collected from 2008-2009 from the Nejanilini Lake region of north-central Manitoba, Canada.